LEGAL REGULATION OF THE USE OF AIR TRANSPORT ACCORDING TO MULTIMODAL TRANSPORTATION AGREEMENTS: CERTAIN ASPECTS - Хом’яченко, Світлана Іванівна; Хоцяновська, Наталя Францівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: had research and had analyzed certain aspects and problems of legal regulation of the use of air transport according to multimodal transportation agreements in Ukraine. Methods: in the work had used the dialectical method of cognition, general scientific and special methods. In particular, structural-functional, deductive and comparative legal methods. Results: summarize recommendations regarding the direction of improving the legal regulation of the use of air transport according to multimodal transportation agreements in Ukraine. Discussion: directions for improving the legal regulation of the use of air transport according to multimodal transportation agreements in Ukraine. Effective use of air transportation as part of multimodal transportation can increase Ukraine’s competitiveness in the international market. However, in Ukraine, there is a disproportion in the volume of transportation by air and other modes of transport. The national legislation of Ukraine does not regulate the relations of multimodal transport practically, so it needs improvement and reform. This study analyzes existing legislation, draft laws and the results of their discussions. As a result, separate recommendations were made regarding the directions of development of legislation in the field of use of aviation transport according to multimodal transport agreements. The main directions of modernization of the legal regulation of the use of aviation transport in multimodal transportations are: unification of terminology used in the legislation with existing international standards, development and introduction into the legislation of Ukraine of the concept of multimodal transportations and its definitions, addition of the existing legislation, transportation using air transport to agree on a single transport document, the legal status of the shipment terminal complexes, the legal status of the subject-matter of these relations, the division of responsibilities of the participants of such transportation, as well as many other issues that need further discussion.